2008
DOI: 10.1177/0363546508318191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neutral-Cushioned Running Shoes on Plantar Pressure Loading and Comfort in Athletes with Cavus Feet

Abstract: Regional differences in pressure reduction suggest neutral-cushioned running shoe recommendation should shift from being categorical in nature to being based on location of injury or elevated plantar pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 30 publications
2
20
0
13
Order By: Relevance
“…The authors reported that ALD taping reduced muscle activity of the tibialis anterior and the tibialis posterior during walking, in subjects with and without exercise-related lower limb pain. 14,15 Plantar pressure measurements have been used widely in biomechanical research to record and describe the changes associated with various interventions, such as footwear, 42 foot orthoses, 33 and foot taping. 41 In-shoe plantar pressure measurements give us evidence of changes in foot kinetics that occur inside footwear during any given task.…”
mentioning
confidence: 99%
“…The authors reported that ALD taping reduced muscle activity of the tibialis anterior and the tibialis posterior during walking, in subjects with and without exercise-related lower limb pain. 14,15 Plantar pressure measurements have been used widely in biomechanical research to record and describe the changes associated with various interventions, such as footwear, 42 foot orthoses, 33 and foot taping. 41 In-shoe plantar pressure measurements give us evidence of changes in foot kinetics that occur inside footwear during any given task.…”
mentioning
confidence: 99%
“…Jordan and Bartlett (1995) found no relationship when assessing walking in casual footwear, whilst Che et al (1994) did find a relationship between the integral and the peak of pressure and comfort feedback when walking in running shoes. However, comfort feedback when running in running shoes did not show sensitivity to plantar pressure changes (Braunstein et al, 2015;Che et al 1994;Dinato et al 2014;and Wegener et al, 2008). Indeed, Braunstein et al (2015) and Dinato et al (2014), who used similar methods to the current study, found no correlation between local plantar pressures and subjective comfort measures in running shoes.…”
Section: Discussionmentioning
confidence: 48%
“…Existing research has studied the relationship between objective global and local plantar pressure measures and subjective self-reported comfort perception measures. Studies on running shoes (Che et al, 1994;Dinato et al, 2014;Wegener et al, 2008) and Casual footwear (Jordan and Bartlett, 1995) have attempted to correlate comfort data of both local foot regions and global overall sensation with peak plantar pressures with inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, Elvira et al (2006), también encuentran la prevalencia del tipo de pie cavo, y concluyen que las actividades desarrolladas en el medio terrestre tienen un plus de carga de trabajo y estrés para el pie, y son necesarias ciertas adaptaciones músculo-esqueléticas en el pie del deportista que tiende a moldearlo creando un arco plantar más elevado que las personas sedentarias. Además si el ejercicio físico es repetitivo y se mantiene durante largos periodos de tiempo tiende a moldear un pie más cavo (Wegener, Burns y Penkala, 2008). Sin embargo, en el presente estudio no se aprecian diferencias entre deportistas y el Grupo de control.…”
Section: Discusionunclassified